Knee Joint Movement Monitoring Device based on Optical Fiber Bending Sensor - Salim, G.M.; Zawawi, M.A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper discusses the possible implementation of an optical fiber bending sensor for knee joint monitoring application. The studied technique is based on the use of an intensity modulated optical fiber via angular displacement between two separated fibers, which approach has been implemented previously in spine movement and respiration rate measurement. To estimate the suitability of this technique for knee monitoring application, the maximum range of detection of the sensor is estimated using the output intensity equation for plastic optical fiber. Based on the estimated output intensity graph with respect to bending angle, it is concluded that the aimed technique is not perfectly suitable for the knee monitoring due to limited sensor’s range of motion, which renders a limited the sensor detection range for knee joint movement. In addition to this, several other types of knee joint monitoring devices are also presented and summarized in a table form to highlight the contribution of other devices.